TOMATO PRODUCTION QUANTITY ESTIMATES FOR 2023-2027 WITH ARIMA MODEL: EVIDENCE FROM LEADING PRODUCING COUNTRIES INCLUDING TURKEY - Adem AKSOY; Haluk Çağlar KAYMAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A study was conducted to analyze the changes in tomato production, which holds significant global importance, from 1961 to 2022 and to provide forward-looking predictions. The primary data for this study were derived from statistics obtained from the Food and Agriculture Organization (FAO) spanning the years 1961 to 2022. Utilizing the ARIMA model, the study aimed to forecast trends in tomato production from 2023 to 2027. The most suitable ARIMA models selected for China, India, Turkey, the United States, and Egypt were (1,1,3), (4,1,3), (2,1,0), (5,1,1), and (4,1,3), respectively. Upon comparing the actual production figures from the period 2018-2022 with the forecasted results for the period 2023-2027, a 4.09% increase in global tomato production is anticipated. Analysis of production forecasts for leading countries during the 2023-2027 period suggests that China, India, and Turkey are expected to experience production growth. Notably, a 7.38% decrease in production is forecasted for the United States during these years. The analytical findings indicate a strengthening influence of China and India in the tomato production sector in the forthcoming years. To enhance competitiveness in the tomato industry, countries like Turkey must focus on reducing production costs while ensuring the production of high-quality goods.